Critical discourse analysis - Locke, Terry, 1946- (New York ; London : Continuum, 2004)
"This introductory text explains the use of critical discourse analysis (CDA) as a research methodology. Beginning with an overview of the key words and theories behind CDA and how these can be used in research, Terry Locke proceeds to provide a demonstration of the application of these theories to both the interpretation of print text and the analysis of conversations. This book is an essential guide for students encountering CDA for the first time."--BOOK JACKET.
1. A close-up on text -- 2. Language, discourse and context -- 3. The critical turn : making discourse analysis critical -- 4. The question of metalanguage in CDA -- 5. Analysing a print text -- 6. Analysing oral texts.
Includes bibliographical references.
Keywords: Research -- Methodology